Society and the supernatural in Song China - Davis, Edward L. (Book collections on Project MUSE., 2001)
Society and the Supernatural in Song China is at once a meticulous examination of spirit-possession and exorcism in the twelfth and thirteenth centuries and a social history of the full panoply of China's religious practices and practitioners at the moment when she was poised to dominate the world economy. Although the Song dynasty (960-1276) is often identified with the establishment of Confucian orthodoxy, Edward Davis demonstrates the renewed vitality of the dynasty's Taoist, Buddhist, and local religious traditions.